Optimizing IABP–patient interaction in VA-ECMO via transcranial doppler - Yepes-Velasco, Andres Felipe; Moreno-Araque, Jeimy Lorena; Garzon-Posada, Natalia (The Ultrasound Journal, 2025)
Background: Patients supported with veno-arterial extracorporeal membrane oxygenation may receive an intra-aortic balloon pump to reduce left ventricular afterload and improve aortic diastolic pressure. However, the effect of this combined mechanical support on cerebral hemodynamics is not uniform and can be influenced by intra-aortic balloon pump timing. Bedside transcranial Doppler offers a rapid, noninvasive way to detect maladaptive cerebral flow patterns and to guide patient–device interaction in real time. Case presentation: We describe a postcardiotomy adult patient on peripheral veno-arterial extracorporeal membrane oxygenation with concomitant intra-aortic balloon pump assistance (1:1) who developed a reduction in cerebral oximetry. Transcranial Doppler of the middle cerebral artery showed increased pulsatility and reduced diastolic velocity, findings consistent with a transient decrease in cerebral perfusion pressure and compatible with balloon deflation asynchrony. Temporary suspension of balloon assistance improved the waveform. Deflation was then synchronized with the electrocardiogram so that it was completed at the onset of systole. Repeat transcranial Doppler performed minutes later showed restoration of diastolic flow and a lower pulsatility index, while extracorporeal support was maintained unchanged and the patient remained hemodynamically stable. Conclusions: In patients receiving veno-arterial extracorporeal membrane oxygenation and intra-aortic balloon pump support, cerebral blood flow may deteriorate if balloon timing is not aligned with the native cardiac cycle. Transcranial Doppler can detect these timing-related neurohemodynamic alterations at the bedside and can confirm their reversibility after simple, ECG-guided optimization of deflation. Integrating transcranial Doppler into multiparametric monitoring may help personalize mechanical circulatory support and protect cerebral perfusion in this high-risk population.